On the Relation Between Gröbner and Pommaret Bases. - Mall, Daniel
The reduced Pommaret basis and the reduced Gröbner basis of an ideal I with respect to a fixed admissible term order ≺ differ in general. A necessary and sufficient criterion for the coincidence of these bases is given.
Keywords: Pommaret bases; Gröbner bases; Stable ideals; Borel ideals